Developing Socio Cultural-Based English Teaching Content Using Dick & Carey Model - Yosef Paseli Dheghu; Rosdiana Mata; Paula Rita (Politeknik Negeri Padang, 2019)
This research is designed in the form of research and development (R & D). It aims to develop an English Textbook for Junior High School students based on Social - Cultural of Ngada Flores. The Textbook is designed to include the cultural scope of Ngada Flores in the teaching materials. The subject matter is theme-based, in which each unit consists of themes drawn from the culturalcoverageofNgadaFlores. The learning model used in this development is the Dick & Carey model, this model has ten strategic steps that is; (1) identify the general objectives of the learning, (2) carry out the learning analysis (3) identify the input behavior and characteristics of the students (4) formulate the objectives of the work (5) develop the benchmark reference materials (6) develop the learning strategy (7) and selecting learning materials (8) designing and executing formative evaluations (9) revising learning materials and (10) designing and executing summative evaluations. The result of study, in general, the comments and suggestions from the content experts stated that the development product of socio cultural-based English textbook provided with pictures and illustration was sufficient, taking it from the correctness, comprehensiveness, and accuracy aspects. The explanation on the learning content was self-explanatory, adequate disclosure and congruent, and significance to the characteristics of SMP students. The students’ assessment and comments described that they were interested and appreciated this textbook development product due to its representative content description, organized, relevance with the local culture, using simple and familiar language with attractive pictures that enhanced their motivation and curiousity in learning individually or in group.